The role of hepatectomy for synchronous liver metastases from pancreatic adenocarcinoma. (December 2018) - Andreou, Andreas; Knitter, Sebastian; Klein, Fritz; Malinka, Thomas; Schmelzle, Moritz; Struecker, Benjamin; Schmuck, Rosa B.; Noltsch, Alina Roxana; Lee, Daniela; Pelzer, Uwe; Denecke, Timm; Pratschke, Johann; et al.
Abstract: Background: The role of hepatectomy for patients with liver metastases from ductal adenocarcinoma of the pancreas (PLM) remains controversial. Therefore, the aim of our study was to examine the postoperative morbidity, mortality, and long-term survivals after liver resection for synchronous PLM. Methods: Clinicopathological data of patients who underwent hepatectomy for PLM between 1993 and 2015 were assessed. Major endpoint of this study was to identify predictors of overall survival (OS). Results: During the study period, 76 patients underwent resection for pancreatic cancer and concomitant hepatectomy for synchronous PLM. Pancreatoduodenectomy, distal pancreatectomy, and total pancreatectomy were performed in 67%, 25%, and 8% of the patients, respectively. The median PLM size was 1 (1–13) cm and 36% of patients had multiple PLM. The majority of patients (96%) underwent a minor liver resection. After a median follow-up time of 130 months, 1-, 3-, and 5-year OS rates were 41%, 13%, and 7%, respectively. Postoperative morbidity and mortality rates were 50% and 5%, respectively. Preoperative and postoperative chemotherapy was administered to 5% and 72% of patients, respectively. In univariate analysis, type of pancreatic procedure (P = .020), resection and reconstruction of the superior mesenteric artery (P = .016), T4 stage (P = .086), R1 margin status at liver resection (P = .001), lymph node metastases (P = .016), poorly differentiated cancer (G3) (P = .037), no preoperative chemotherapy (P = .013), and no postoperative chemotherapy (P = .005) were significantly associated with worse OS. In the multivariate analysis, poorly differentiated cancer (G3) (hazard ratio [HR] = 1.87; 95% confidence interval [CI] = 1.08–3.24; P = .026), R1 margin status at liver resection (HR = 4.97; 95% CI = 1.46–16.86; P = .010), no preoperative chemotherapy (HR = 4.07; 95% CI = 1.40–11.83; P = .010), and no postoperative chemotherapy (HR = 1.88; 95% CI = 1.06–3.29; P = .030) independently predicted worse OS. Conclusions: Liver resection for PLM is feasible and safe and may be recommended within the framework of an individualized cancer therapy. Multimodal treatment strategy including perioperative chemotherapy and hepatectomy may provide prolonged survival in selected patients with metastatic pancreatic cancer. Highlights: Liver resection for pancreatic liver metastases is feasible and safe. Liver resection for PLM may be recommended within the framework of an individualized cancer therapy. Multimodal treatment including chemotherapy and hepatectomy may provide prolonged survival in selected patients with PLM.